Improving Dual-Task Walking Paradigms to Detect Prodromal Parkinson’s and Alzheimer’s Diseases - Belghali, Maroua; Chastan, Nathalie; Davenne, Damien; Decker, Leslie M. (Frontiers in Neurology, 2017)
Gait control is a complex movement, relying on spinal, sub-cortical, and cortical structures. The presence of deficits in one or more of these structures will result in changes in gait automaticity and control, as is the case in several neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease. By reviewing recent findings in this field of research, current studies have shown that gait performance assessment under dual-task conditions could contribute to predict both of these diseases. Such suggestions are relevant mainly for people at putatively high risk of developing Alzheimer’s disease (i.e., older adults with Mild Cognitive Impairment subtypes) or Parkinson’s disease (i.e., older adults with either Mild Parkinsonian signs or LRRK2 G2019S mutation). Despite the major importance of these results, the type of cognitive task that should be used as a concurrent secondary task has to be selected among the plurality of tasks proposed in the literature. Furthermore, the key aspects of gait control that represent sensitive and specific “gait signatures” for prodromal Alzheimer’s disease or Parkinson’s disease need to be determined. In the present perspective article, we suggest the use of a Stroop interference task requiring inhibitory attentional control and a set-shifting task requiring reactive flexibility as being particularly relevant secondary tasks for challenging gait in prodromal Alzheimer’s disease and Parkinson’s disease, respectively. Investigating how inhibition and cognitive flexibility interfere with gait control is a promising avenue for future research aimed at enhancing early detection of Alzheimer’s disease and Parkinson’s disease, respectively.